2015
DOI: 10.1260/2040-2295.6.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Hospitals’ Adaptive Capacity during a Loss of Infrastructure Services

Abstract: Resilience in hospitals - their ability to withstand, adapt to, and rapidly recover from disruptive events - is vital to their role as part of national critical infrastructure. This paper presents a model to provide planning guidance to decision makers about how to make hospitals more resilient against possible disruption scenarios. This model represents a hospital's adaptive capacities that are leveraged to care for patients during loss of infrastructure services (power, water, etc.). The model is an optimiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…However, the indicators that described the structural and nonstructural characteristics as well as administrative and functional activities concerning structural and nonstructural systems included in this study. Most of the studies focused more on electrical and water utilities and transportation networks in hospitals [40,42,46,51,53,54,56,58,64]. The literature showed that other utilities in hospitals like communication system, gas supply system, sewage system as well as non-structural components of buildings, such as architectural elements have been less considered.…”
Section: Discussionmentioning
confidence: 99%
“…However, the indicators that described the structural and nonstructural characteristics as well as administrative and functional activities concerning structural and nonstructural systems included in this study. Most of the studies focused more on electrical and water utilities and transportation networks in hospitals [40,42,46,51,53,54,56,58,64]. The literature showed that other utilities in hospitals like communication system, gas supply system, sewage system as well as non-structural components of buildings, such as architectural elements have been less considered.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this aim, the included articles concentrated on the importance of hospital resilience by surveying the building and utility situation in disasters, but most of them focused more on electrical and water utilities and transportation networks in hospitals (28,30,35,42,44,46,48,50,59). It showed that other utilities in hospitals like communication system, gas supply system, sewage system and also non-structural components of buildings such as architectural elements have been less considered.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the indicators that described the structural and non-structural characteristics and also administrative and functional activities concerning structural and non-structural systems included in this study. Most of the articles focused more on electrical and water utilities and transportation networks in hospitals (34,36,40,47,49,50,52,54,60). The literature showed that other utilities in hospitals like communication system, gas supply system, sewage system and also non-structural components of buildings such as architectural elements have been less considered.…”
Section: Thematic Analysismentioning
confidence: 99%